STRATEGIC MANAGEMENT AS TOOL FOR IMPROVEMENT OF MANAGEMENT OF FINANCES IN UKRAINE - Daudova, G.; Kovalchuk , V.; Kurnosov, O. (Pressing Problems of Public Administration, 2019)
Restoration of the macroeconomic stability in Ukraine requires introduction of advanced budget planning and strategic management, which would determine new approaches to realizing systemic changes in the country’s economy, providing predictable tax, debt-management and budget policies, predictability of budget expenditures and financial stability.Practical elaborations in the sphere of effective management of finances make it possible to assert the necessity of further improvement of budget planning. It is stipulated by the lack of probable indices related to middle-term distribution of revenues and expenditures among the levels of the budget system, which makes it impossible to provide measures of socio-economic development of territories to be realized with adequate financial resources. The paper objective is research of the issue of introducing strategic management into the process of forecasting and planning, determining strategic planning principles, and providing substantiated proposals as to improvement of the financial management mechanism.One of the important aspects of public funds transformation is strategic management that presupposes application of a systemic approach to shaping a predictable budget policy.A basic component of strategic management is national-level strategic planning of socio-economic activity, which makes it possible to establish long-term priorities.The major condition of budget planning, budget stability, transparency and openness of budgeting is a high-quality macroeconomic forecasting.Being based on the predictability of the country’s long-term economic development, strategic management becomes a tool for laying the foundation for profound systemic reforms, ensuring financial stability and boosting middle-term economic growth.In order to determine the impact of individual factors on the planned indices, it is expedient to consider several scenarios of macroeconomic forecasts which represent the response of the economy to the reforms and measures taken, as well as those planned.Involvement of research institutions which are independent of the government in analyzing forecasts would allow obtaining the most reliable version of strategic indices.Under the conditions of certain challenges, it seems most timely to introduce a system of managing an expanded range of risks.In practice, realization of the main directions of budget policy testifies to the need for introducing strategic management aimed at determining an adequate forecasting of macroeconomic indices of the country’s economic and social development. The main elements that form an integral part of middle-term planning are as follows: probable income measures, financial provision of expenditures and establishing their threshold amount, considering forecasted indices according to several scenarios, their monitoring and a continuous control over the macroeconomic situation.